ANALISIS PRODUK ROTI BAKAR AZHARI MENGGUNAKAN SIX SIGMA DAN KAIZEN PADA PENGENDALIAN KUALITAS PRODUK - Rafly Maulana Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Azhari Bakar Bread Factory is an MSME that has been engaged in the production of toast since 2016. In the production process, defects were still found on February 27 – March 27 2024. The Azhari Bakar Bread Factory produced 12,551 pieces of toast, consisting of 205 pieces of torn bread. and 92 slices of burnt bread. Based on the above problems, it can be solved using the six sigma and Kaizen methods through the DMAIC (define, Measure, Analyze, Improve, Control) stages, with the Improve stage using the Five M-checklist method and the Control stage using the Five Step Plan (6s movement) method. to control quality from the initial process until recommendations for improvement are found. Based on the calculation results, it has a sigma level of 2.488 with a defect per million opportunities (DPMO) result of 12,000 and a Defect Per Opportunities (DPO) result of 0.012. Based on the Pareto diagram, the most dominant percentage of defects is torn bread defects at 69% and toasted bread defects at 31%. The proposed improvements are to ventilate the air, make improvements by providing a timer feature on the oven machine, purchase digital measuring equipment, reorganize the production area and create symbols in the storage area as well as create a working hours and rest schedule.